A curvature-compensated CMOS bandgap with negative feedback technique. (June 2016) - Li, Xiaochao; Zhou, Liangxi; Chen, Yihui; Zhang, Ying; Cao, Chunhui; Guo, Donghui
Abstract: This paper propose a novel high-order curvature-corrected CMOS bandgap reference (BGR) utilizing the negative feedback structure. The innovative negative feedback bandgap core not only compensates the exponential nonlinearity of VBE but also improves the power supply rejection ratio (PSRR) and line regulation. The proposed BGR is analyzed and implemented in 0.35-μm CMOS process. Experimental results of the BGR indicate that a minimum temperature coefficient (TC) of 13 ppm/°C @−40 °C to 180 °C, a PSRR of −64 dB @ 100 Hz, and the 5.2 uV/V line regulation (LNR) from 3 V to 3.6 V supply voltage at room temperature. The active area of the presented BGR is 133 μm×300 μm. Graphical abstract: In this paper, we proposed a new circuit configuration to improve a BGR׳s TC as well as the PSRR. The circuit adopt a negative feedback in the first-order voltage reference core area for a curvature corrected compensation and high PSRR. Till now, no bandgap voltage reference based on this technique has proposed in any paper.